Malignant transformation of mesenchymal hamartoma of the liver: case report and review of the literature. - Ramanujam, T.M.; Ramesh, J.C.; Goh, D.W.; Wong, K.T.; Ariffin, W.A.; Kumar, G.; Taib, N.A. (Elsevier, 1999)
Here the first case in the literature of both mesenchymal hamartoma and malignant mesenchymoma occurring in a 6-year-old male child, at different times and at different sites in the liver, and also the possible malignant transformation of a mesenchymal hamartoma is reported. The tumor developed from a lesion in the right lobe that was overlooked initially during a left lateral segmentectomy at 18 months of age for a mesenchymal hamartoma. Malignant mesenchymoma is a rare and aggressive tumor. The origin of this tumor is not well understood. There has been no direct support to the hypothesis that malignant mesenchymoma may be the malignant counterpart of mesenchymal hamartoma. The authors provide clinical and histopathologic evidence in our case that suggests the possibility of malignant mesenchymoma arising from a mesenchymal hamartoma. This case emphasizes the need for complete removal of mesenchymal hamartoma and the need for long-term follow-up to detect multifocal lesion or malignant transformation.